Experimental and theoretical evaluation of a sound absorbing plaster - Kilander, Fredrik (My University, 2004)
A Kundt's tube was used to measure the sound absorption of a porous fibreous plaster for different thicknesses and surface smoothnesses. Measurements were also done with the plaster in a multi layer absorbing system together with a layer of air and porous absorber backed by a hard wall. Frequencies up to 4 kHz was included and the results compared to an empirical model by Delany and Bazely. This model predicts the acoustical impedance of isotropic homogenous materials made of fibers from two parameters, the flow resistivity and frequency. The flow resistivity for the plaster was determined to 400 x 103 (Ns/m4) by curve fitting between measured values and the model and then used for optimize the thickness of an air layer in a three layer absorber. It was found that an air layer of 10-20cm closest to the hard surface in a multilayer plaster/absorber/air/hard backing absorber increases low frequency absorption. If the plaster is applied directly on a hard suface a thicker layer absorbs sound better than a thin. When applied on a underlayer of porous absorber a thin layer is better. A rough surface of the plaster absorbs sound slightly better than a polished at high frequencies.
Keywords: Samhällsbyggnadsteknik; Civil Engineering